Genetic Diversity of Brucella melitensis in Kazakhstan in Relation to World-Wide Diversity - Shevtsova, Elena; Vergnaud, Gilles; Shevtsov, Alexandr; Shustov, Alexandr; Berdimuratova, Kalysh; Mukanov, Kasim; Syzdykov, Marat; Kuznetsov, Andrey; Lukhnova, Larissa; Izbanova, Uinkul; Filipenko, Maxim; Ramankulov, Yerlan (Frontiers in Microbiology, 2019)
We describe the genetic diversity of 1327 Brucella strains from human patients in Kazakhstan using multiple-locus variable-number tandem repeat (VNTR) analysis (MLVA). All strains were assigned to the B. melitensis East Mediterranean group and clustered into 16 MLVA11 genotypes, nine of which are reported for the first time. MLVA11 genotype 116 predominates (86.8%) and is present all over Kazakhstan indicating existence and temporary preservation of a “founder effect” among B. melitensis strains circulating in Central Eurasia. The diversity pattern observed in humans is highly similar to the pattern previously reported in animals. The diversity observed by MLVA suggested that the epidemiological status of brucellosis in Kazakhstan is the result of the introduction of a few lineages, which have subsequently diversified at the most unstable tandem repeat loci. This investigation will allow to select the most relevant strains for testing these hypotheses via whole genome sequencing and to subsequently adjust the genotyping scheme to the Kazakhstan epidemiological situation.